Bariatric Surgery in Moderately Obese Patients: A Prospective Study. (24th December 2013) - Cerci, M.; Bellini, M. I.; Russo, F.; Benavoli, D.; Capperucci, M.; Gaspari, A. L.; Gentileschi, P.
Abstract : Introduction . Moderate obesity (BMI 30–35 kg/m 2 ) affects 25% of the western population. The role of bariatric surgery in this context is currently debated, reserved for patients with comorbidity, as an alternative to conservative medical treatment. We describe our experience in moderately obese patients treated with bariatric surgery. Materials and Methods . Between September 2011 and September 2012, 25 patients with grade I obesity and comorbidities underwent bariatric surgery: preoperative mean BMI 33.2 kg/m 2, 10 males, mean age 42 years. In presence of type 2 diabetes mellitus (T2DM) (56%), gastric bypass was performed; in cases with hypertension (64%) and obstructive sleep apnea (OSA) (12%), sleeve gastrectomy was performed. All operations were performed laparoscopically. Results . Mean follow-up was 12.4 months. A postoperative complication occurred: bleeding from the trocar site was resolved with surgery in local anesthesia. Reduction in average BMI was 6 points, with a value of 27.2 kg/m 2 . Of the 14 patients with T2DM, 12 (86%) discontinued medical therapy because of a normalization of glycemia. Of the 16 patients with arterial hypertension, 14 (87%) showed remission and 2 (13%) improvement. Complete remission was observed in patients with OSAS. Conclusions . The results of our study support the validity of bariatric surgery in patients with BMI 30–35 kg/m 2 . Our opinion is that, in the future, bariatric surgery could be successful in selected cases of moderately obese patients.